Tenecteplase versus alteplase for intravenous thrombolysis of acute ischemic stroke patients with large-vessel occlusion: a systematic review and meta-analysis - Yao, Beibei; Wang, Xintong; Wu, Yao; Zhu, Qing; Li, Li; Tang, Xiaogang; Wu, Minghua (Frontiers in Neurology, 2025)
BackgroundTenecteplase (TNK) was found non-inferior to alteplase (ALT) for acute ischemic stroke (AIS). We sought to further elucidate the efficacy and safety of intravenous TNK versus ALT for AIS patients with large-vessel occlusion (LVO).MethodsWe systematically searched PubMed, Embase, Web of Science, and https://clinicaltrials.gov/ till 20 January 2024 for randomized controlled clinical trials (RCTs) comparing TNK with ALT in AIS patients with LVO. The quality of the included studies was estimated using the Cochrane Risk of Bias Tool. Pooled analysis and publication bias were conducted using RevMan 5.3 and Stata 15. Risk ratios (RRs) with 95% confidence intervals (95% CIs) were reported for each outcome measure. The primary outcome was excellent neurological recovery, which was defined as a modified Rankin Scale (mRS) score of 0–1 at 90 days, and safety outcomes included any parenchymal hematoma, sympomatic intracerebral hemorrhage, and 3-month death.ResultsFive RCTs enrolling 1,028 patients were included. There were no significant differences in terms of 90-day excellent neurological recovery (RR 1.18; 95% CI 1.00–1.40; p = 0.05), good neurological recovery (RR 1.18; 95% CI 0.90–1.54; p = 0.23), early neurological improvement (RR 1.00; 95% CI 0.57–1.77; p = 1.00), or successful reperfusion (RR 1.15; 95% CI 0.93–1.44; p = 0.20). In addition, no significant differences were observed in safety outcomes, including any parenchymal hematoma (RR 1.01; 95% CI 0.70–1.45; p = 0.98), symptomatic intracerebral hemorrhage (RR 1.14; 95% CI 0.62–2.10; p = 0.68), or 3-month mortality (RR 1.22; 95% CI 0.52–2.84; p = 0.65).ConclusionTNK is an alternative to ALT for thrombolysis in AIS patients with confirmed LVO, offering lower cost and easier administration without increasing safety concerns.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024540215.